Sistem Pakar untuk Menentukan Kualitas Biji Kopi Komersial dengan Metode Forward Chaining - Ariyanto, Atun; Listiani, Vita; Firmansyah, Nanda Azizan; Purnomo, Alif; Firdayanti, Agustina; Yunita, Farida (Department of Information Technology, Universitas Timor, Indonesia, 2024)
Abstract – This research aims to create an expert system plan to determine the quality of commercial coffee beans using the Forward Chaining method. This method was chosen because it is able to process data from initial facts to reach conclusions based on a sequence of specific steps in evaluating coffee beans. This system is designed to assist farmers in selecting quality commercial coffee beans according to established criteria. The data collection technique was carried out through direct interviews with coffee experts in the Ketep area, Magelang Regency, in order to obtain information about the characteristics of coffee beans that influence their quality.